Resepsi Ayat-ayat Thoharoh dan Isrof dalam Pengelolaan Sumber Daya Air dan Sampah di Pondok Pesantren Sirojul Ulum Semanding - M. Miftahun Najib; M. Ulil Abshor (AR ROSYAD: Jurnal Keislaman dan Sosial Humaniora, 2025)
This study examines the reception of Qur’anic verses on ṭahārah (purification) and isrāf (wastefulness) in the management of water resources and waste at Sirojul Ulum Islamic Boarding School in Semanding. The research is based on the observation that santri’s understanding of Qur’anic teachings often remains theoretical, thus requiring a study on how these verses are received and practiced in daily life. This study employs the Living Qur’an approach with a qualitative-descriptive method through observation, interviews, and documentation. The findings indicate that the reception of ṭahārah is reflected in maintaining environmental cleanliness, conserving water during ablution, and promoting awareness of purity in worship practices. Meanwhile, the reception of isrāf is manifested in waste reduction, proportional use of goods, and sustainable waste management. This reception is not only textual but also functional and practical, forming an ecological ethic rooted in Qur’anic values. Therefore, this research emphasizes the strategic role of Islamic boarding schools in internalizing Qur’anic teachings towards a clean, efficient, and sustainable lifestyle.